Hide and seek - Allington, Richard L. (Illinois : Scott, Foresman, 1985)
Literature book for young readers. Section One: Making Friends, Section Two: Going Places, Section Three: Finding Out. Includes Pictionary, Word Lists, and Poetry
Primary
Keywords: Reading (Elementary); Reading (Primary); Readers (Elementary); Reading -- Remedial teaching; Education, Primary; Language arts (Primary)